The impact of herpes zoster infection awareness program on myths, knowledge, and practices among the rural population of western Maharashtra - Goyal, Sagar; Salgar, Akshay; Dhavalshankh, Gayatri G.; Dhavalshankh, Ganesh P.; Dhavalshankh, Archana G. (International Journal Of Community Medicine And Public Health, 2024)
Background: In India, there is a paucity of population-based studies and data on herpes zoster in reporting herpes zoster cases. Several shreds of evidence reflect that the disease causes a burden on population health in India. Besides several known risk factors, myths, lack of knowledge, attitude, and practices towards treating this infection may affect the quality of life and disease burden. Imparting knowledge, awareness regarding myths and misconceptions, and early approaches for treatment can help prevent disease and complications in the population. Methods: Our study variables were myths about herpes zoster infection, knowledge about herpes zoster infection, and attitudes and practices towards the treatment of herpes zoster infection and to evaluate the impact of health awareness programme on it. It is an interventional study where study population is the families of adopted villages by D.Y. Patil Medical College, Kolhapur from the rural population of western Maharashtra. Results: The awareness programme which was the intervention in this study, was effective in increasing the awareness about myths and knowledge about herpes zoster infection as well as positive impact related to treatment practices for herpes zoster infection among the rural population in the adapted villages in western Maharashtra. Conclusions: The awareness programme which was the intervention in this study, was effective in increasing the awareness about myths and knowledge about herpes zoster infection as well as positive impact related to treatment practices for herpes zoster infection among the rural population in the adapted villages in western Maharashtra.